2015
DOI: 10.1121/1.4920384
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cochlear health for cochlear-implant function

Abstract: In humans with cochlear implants, functional measures show considerable variation from one stimulation site to another along the electrode array. Our research has demonstrated that (1) the across-site patterns of the functional data are stable over time but differ across subjects; and (2) the across-site patterns are measure specific. These observations are consistent with the hypotheses that implant performance at a given stimulation site is dependent on specific conditions near the site, and that the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…The impairment peaked around 5 to 9 days after implant insertion, consistent with a model in which an inflammatory reaction grows over time and then dissipates. Several previous studies have shown that the slopes of amplitude-growth functions of electrophysiological potentials in response to electrical stimulation are correlated with the number of surviving auditory neurons (Smith and Simmons, 1983; Hall, 1990; Pfingst et al, 2014). It is unlikely that the number of SGNs decreased and then increased following implant insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment peaked around 5 to 9 days after implant insertion, consistent with a model in which an inflammatory reaction grows over time and then dissipates. Several previous studies have shown that the slopes of amplitude-growth functions of electrophysiological potentials in response to electrical stimulation are correlated with the number of surviving auditory neurons (Smith and Simmons, 1983; Hall, 1990; Pfingst et al, 2014). It is unlikely that the number of SGNs decreased and then increased following implant insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Further, listener factors may limit perception. These listener factors include: (a) variable patterns of nerve survival; (b) electrode array position; and (c) residual acoustic hearing (Bierer and Faulkner, 2010;Limb and Roy, 2014;Pfingst et al, 2015). At the central processing level, there may be extensive changes in the brain as a result of auditory deprivation (Stropahl et al, 2017) as well as altered general cognitive abilities (Holden et al, 2013;Kramer et al, 2018).…”
Section: Implications For Cochlear Implant Usersmentioning
confidence: 99%
“…The inner ear's spiral ganglion's myelinated bipolar neurons (SGNs) provide the conduit for sensory messages from peripheral sensory receptors of mechanosensory hair cells to the central neurons in auditory brain stem nuclei. When the hair cells in the organ of Corti are lost or incapacitated, due to injury, aging, or loss of function resulting from genetic disorders, SGNs lose their peripheral targets and can progressively degenerate, so that the remaining neurons are less capable of functional interaction with either the remaining sensory organ of Corti hair cells or with a cochlear implant/prosthesis (Pfingst et al, , review). Although SGN loss in humans is less pronounced than in animal models of hair cell loss or knockout mouse models of hair cell loss (Bermingham‐McDonogh and Rubel, ; Bodmer, ; Breuskin et al, ), it appears that even if SGNs remain as long as 40 years post‐onset of deafness, their functionality can be impaired (Sato et al, ; Wise et al, ; Jiang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of cochlear implants, a variety of different strategies to improve hearing perception are being tested, including advanced engineering of cochlear implant devices, which can communicate well with the brain stem (Pfingst et al, , review); cell‐replacement therapies, involving various types of stem cells to augment or substitute for lost or malfunctioning neurons (Corrales et al, ; Coleman et al, : Reyes et al, ; Chen et al, ); regrowing spiral ganglion neuronal processes to improve connections with the implant and concomitantly reduce the distance between them (Altschuler et al, ); “classical” neurotrophin‐releasing Schwann cells used to “coat” cochlear implants have been shown to enhance neurite contacts with the devices (O'Leary et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation